1996
DOI: 10.1002/(sici)1097-0215(19961115)68:4<424::aid-ijc4>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Detection of nonprostatic PSA in serum and nonserum samples from women

Abstract: Prostate-specific antigen (PSA) has been characterized as a specific prostate marker, although recent studies have suggested the existence of PSA of nonprostatic sources. We have assessed the presence of PSA by an ultrasensitive assay in 276 serum and nonserum samples from women. Our data show the presence of PSA in 90% of nonserum samples, including milk secretions, breast cysts, amniotic fluids and broncho-alveolar washings. We have also detected its presence in 58% of the sera tested, although it only excee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 16 publications
2
22
0
Order By: Relevance
“…In the present study, elevation of total PSA was detected only in 7% of the fibroadenoma and in none of the mastopathy patients. This shows that elevated serum total PSA levels are not a consistent finding in patients with benign breast disease, which is in accordance with a previous report (Filella et al, 1996). The discrepancies between these results and previous findings (Borchert et al, 1997a(Borchert et al, , 1997b may be due to the selection of the patients, differences in the normal control groups (e.g.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In the present study, elevation of total PSA was detected only in 7% of the fibroadenoma and in none of the mastopathy patients. This shows that elevated serum total PSA levels are not a consistent finding in patients with benign breast disease, which is in accordance with a previous report (Filella et al, 1996). The discrepancies between these results and previous findings (Borchert et al, 1997a(Borchert et al, , 1997b may be due to the selection of the patients, differences in the normal control groups (e.g.…”
Section: Discussionsupporting
confidence: 86%
“…Abbreviations as in Table 1; NA = not analysed as fibroadenomas and breast cysts (Borchert et al, 1997a;Borchert et al, 1997b). However, discordant data concerning the clinical significance of PSA immunoreactivity in breast tumour cytosols (Astill et al, 1996;Dibbelt et al, 1996;Wu et al, 1995) and in breast cysts (Filella et al, 1996;Lai et al, 1996;Mannello et al, 1996) as well as the diagnostic value of serum total PSA in BC (Giai et al, 1995) and breast cyst disease (Filella et al, 1996) have been presented. Most of the earlier results have been obtained using a time-resolved immunofluorometric (TR-FIA) PSA assay (Borchert et al, 1997b;Diamandis et al, 1994;Ferguson et al, 1996;Melegos and Diamandis, 1996;Yu et al, 1995aYu et al, , 1996Yu et al, , 1998 which is not commercially available.…”
Section: Discussionmentioning
confidence: 99%
“…Prostate Specific Antigen (PSA), a 33 kDa serine protease which has already been established as a valuable marker for screening, diagnosis and management of prostate cancer [2,3] has been suggested to have a number of potential roles in breast cancer. PSA, found in a very low but detectable levels in the circulation of women, is likely to be originated from breast tissue [4]. Similar to prostate PSA, production of breast PSA is said to be under hormonal control and androgens in particular are believed to upregulate the expression of PSA gene through androgen receptor [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have reported detectable PSA in 50 % non pregnant females [2,15,23]. Filella et al [16] used ultrasensitive Fluoro-immunometric assay (detection limit of 0.004 lg/l) detected the presence of PSA in 58 % of the sera tested.…”
Section: Resultsmentioning
confidence: 99%
“…They proposed that normal breast tissue, endometrium and salivary glands are the likely sources of serum PSA. Serum PSA was found to be higher in women of higher age, hispanic women and hirsute women [14][15][16].…”
Section: Introductionmentioning
confidence: 93%